Evidence for unloading arterial baroreceptors during low levels of lower body negative pressure in humans - Fu, Qi; Shibata, Shigeki; Hastings, Jeffrey L; Prasad, Anand; Palmer, M. Dean; Levine, Benjamin D (American journal of physiology. Heart and circulatory physiology, 2009)
1 Institute for Exercise and Environmental Medicine, Presbyterian Hospital of Dallas, and 2 The University of Texas Southwestern Medical Center at Dallas, Dallas, Texas Submitted 21 February 2008 ; accepted in final form 3 December 2008 Low levels (i.e., 20 mmHg) of lower body negative pressure (LBNP) have been utilized to unload "selectively" cardiopulmonary baroreceptors in humans, since steady-state mean arterial pressure and heart rate (HR) have been found unchanged at such levels. However, transient reductions in blood pressure (BP), followed by reflex compensation, may occur without detection, which could unload arterial baroreceptors. The purposes of this study were to test the hypothesis that the arterial baroreflex is engaged even during low levels of LBNP and to determine the time course of changes in hemodynamics. Fourteen healthy individuals (age range 20–54 yr) were studied. BP (Portapres and Suntech), HR (ECG), pulmonary capillary wedge pressure (PCWP) or pulmonary artery diastolic pressure (PDP) and right atrial pressure (RAP) (Swan-Ganz catheter) and hemodynamics (Modelflow) were recorded continuously at baseline and –15- and –30-mmHg LBNP for 6 min each. Application of –15-mmHg LBNP resulted in rapid and sustained falls in RAP and PCWP or PDP, progressive decreases in cardiac output and stroke volume, followed subsequently by transient reductions in both systolic and diastolic BP, which were then restored through the arterial baroreflex feedback mechanism after 15 heartbeats. Additional studies were performed in five subjects using even lower levels of LBNP, and this transient reduction in BP was observed in three at –5- and in all at –10-mmHg LBNP. The delay for left ventricular stroke volume to fall at –15-mmHg LBNP was about 10 cardiac cycles. An increase in systemic vascular resistance was detectable after 20 heartbeats during –15-mmHg LBNP. Steady-state BP and HR remained unchanged during mild LBNP. However, BP decreased, while HR increased, at –30-mmHg LBNP. These results suggest that arterial baroreceptors are consistently unloaded during low levels (i.e., –10 and –15 mmHg) of LBNP in humans. Thus "selective" unloading of cardiopulmonary baroreceptors cannot be presumed to occur during these levels of mild LBNP. baroreflexes; arterial pressure; hemodynamics Address for reprint requests and other correspondence: B. D. Levine, Institute for Exercise and Environmental Medicine, 7232 Greenville Ave., Suite 435, Dallas, Texas 75231 (e-mail: BenjaminLevineatTexasHealth.org )